Willingness to Provide a Hair Sample for Drug Testing among Electronic Dance Music Party Attendees - Palamar, Joseph J. (Subst Abus, 2018)
BACKGROUND: Non-disclosure of drug use on surveys is common and many drug users unknowingly ingest adulterant or replacement drugs, which leads to underreporting of use of these drugs. Biological testing can complement survey research, and hair-testing is an appealing method as many drugs are detectable for months post-use. We examined willingness to donate a hair sample to be tested among those surveyed in a population at high risk for consuming adulterated drugs—electronic dance music (EDM) party attendees. METHODS: We surveyed 933 adults entering EDM parties in New York City in 2017. Hair donation response rates and reasons for refusal were examined from this cross-sectional study. RESULTS: A third (n=312; 33.4%) provided a hair sample. Lack of interest (21.0%), lack of time (19.8%), not wanting a lock of hair cut (17.7%), and disinterest in having hair cut in public (13.8%) were the main reported reasons for refusal. 4.7% refused because they could not receive results. Past-year drug users were more likely to fear identification than non-users (p<.001). Asian participants were at lower odds of providing a hair sample (aOR=0.53, 95% CI=0.32–0.87), and those reporting past-year use of LSD (aOR=1.62, 95% CI=1.11–2.35), opioids (nonmedical; aOR=1.93, 95% CI=1.25–2.99), and/or methamphetamine (aOR=3.43, 95% CI=1.36–8.62) were at higher odds of providing a sample than non-users of these drugs. CONCLUSIONS: Only a third of participants provided a hair sample and we found individual-level differences regarding willingness to provide a sample. Factors contributing to refusal should be considered to increase response rates and generalizability of results.